Accuracy and epistemic agency in Descartes: an exploration of the margins of the First Meditation - Ávila Cañamares, Ignacio (Estudios de Filosofía, 2019)
In this paper I advance a reading of the contours of the First Meditation. I try to bring out an important dimension of Descartes’s thinking about the virtue of accuracy. I contrast the concern for the truth in daily life and in the Cartesian inquiry. I explore the way in which Descartes faces some epistemic risks in the course of his meditation and highlight some aspects of his conception of epistemic agency. And, nally, I conclude with a brief note about Pascal’s wager.